CLIMATE CHANGE COMMUNICATION IN NIGERIA: TOWARDS PROFFERING SUSTAINABLE ALTERNATIVES - OGWEZI, Joyce Ogho; UMUKORO, Ese Steven (International Journal of Psychosocial Rehabilitation, 2020)
Community and global efforts at mitigating climate change have been greatly influenced by the media’s portrayal of climate change inNigeria and sub-Saharan Africa. Mitigation and adaptation measures have also been closely linked to people’s perceptions and understanding gained through daily exposure to media content, individual media consumption and news production by mainstream media. Despite this dependence on media consumption by the people, it has been generally acknowledged that “journalists, especially in the developing world, are not sufficiently equipped to process and effectively communicate climate change information’ in a manner that would galvanise popular participation in climate change mitigation efforts. Even though environmental reporting is fast becoming an important genre of journalism, and environmental consciousness within newsrooms continue to rise, environmental issues associated with climate change have not received the needed attention. With little or no specialisation in many newsrooms across Nigeria, it has become increasingly difficult for journalists to understand the phenomenon, process technical information, as well as sustain narratives on climate change adaptation issues and prospects for integrating them into decision-making. Yet this ability of the media to set the agenda by creating awareness and mobilising media consumers to collective action is right at the centre of all mitigation initiatives. Therefore, these challenges gave rise to this paper which examines: Climate Change Communication in Nigeria: Towards Proffering Sustainable Alternatives.Adopting Agenda setting as a theoretical framework and qualitative research method, the paper gave a detailed evaluation of the concepts of climate change and climate change communication. Also, the principles of climate change communication were exhaustively examined. The paper concluded by recommending an effective approach to climate change communication in Nigeria.